Annually mulched wild flower strips increase the observed wild bee (Apiformes) species richness and abundance in vineyard fallows in the short term - Krahner, André; Maixner, Michael; Porten, Matthias; Schmitt, Thomas (Frontiers in Bee Science, 2024)
Insect conservation through habitat management is particularly important in regions of high biodiversity potential, such as steep-slope viticultural landscapes. Therefore, we studied the effects of realistic options for the conservation of open and flower-rich vineyard fallows on local wild bee communities. Using a fully-crossed factorial design, we sampled bees in 10 vineyard fallows in the Moselle region (SW Germany), which were partially subjected to different treatments (mulching, sowing of wild flower strips, combination, and untreated control). Over two years, we sampled 9323 individuals from 140 bee species with hand netting and pan traps. Based on the hand-netting samples, AICc-based model selection (Generalized Linear Mixed Models) revealed effects of fallow treatment, interacting with sampling year, on the number of sampled bee individuals and on the number of sampled bee species. In the second sampling year, we sampled significantly more individuals in wild flower strips (WFS) as well as in the combination treatment than in the untreated control. Also in the second year, the number of sampled species was significantly higher in the combination treatment than in the mulching treatment, and significantly higher than in the untreated control. Vineyard fallow management can promote bee communities in steep-slope viticultural landscapes, and options involving WFS, especially in combination with an annual mulching, should be preferred over options solely relying on repeated mulching. Moreover, the findings highlight that management options involving WFS need some time after initiation for unfolding their positive effects on bee communities.